(untitled) (Jurnal Bahasa, 2005)
Despite much work on compound words have been done, the debate on this issue is still sizzling. There is no common acceptable definition on compound words due to different of opinions and findings. Some gram-marians use structural criterion in defining the words, while others look at the semantic features. The description becomes more bewildered when phrases and compound words shared the common properties. Consequently, it poses problems in arranging and representing compound words in a dictionary. This article attempts to distinguish between compound words and phrases in Malay by using semantic criteria, namely non-infusibility, non-reversibility and circumfixes as a test in determining compound words especially idioms. The same principles will be applied to analyze ordinary compound words. This article also explains the dis-tinction between compound words with phrases, and accordingly pro-poses their arrangements and representations in the dictionary.